2018
DOI: 10.1093/bfgp/ely020
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine and antibody production in plants: developments and computational tools

Abstract: Plants as bioreactors have been widely used to express efficient vaccine antigens against viral, bacterial and protozoan infections. To date, many different plant-based expression systems have been analyzed, with a growing preference for transient expression systems. Antibody expression in diverse plant species for therapeutic applications is well known, and this review provides an overview of various aspects of plant-based biopharmaceutical production. Here, we highlight conventional and gene expression techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 140 publications
0
24
0
Order By: Relevance
“…Vaccines are basically consisting of different immunogenic ingredients of disease (pathogens), comparatively the whole pathogenic agent 52 . Epitope prediction for antibodies becomes more significant with the advancement of the computational tools for designing a vaccine 53 . In the field of bioinformatics Immuno-informatics is a sub-branch that includes a lot of tools & databases.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines are basically consisting of different immunogenic ingredients of disease (pathogens), comparatively the whole pathogenic agent 52 . Epitope prediction for antibodies becomes more significant with the advancement of the computational tools for designing a vaccine 53 . In the field of bioinformatics Immuno-informatics is a sub-branch that includes a lot of tools & databases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described tobacco-derived plantibodies that showed potent therapeutic activity against multiple viruses such as EBOV, HBV, HIV, PEDV, RABV, WNV, and others in small animal models of infection, e.g., mice [39,[42][43][44][45][46]. However, to our knowledge, this is the first study demonstrating the ability of plantibodies to protect against influenza viral infections.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, plantibodies overcome some of the concerns associated with animal-derived therapeutic MAbs obtained from serum or plasma, including intermediate reactions, pyrogenicity, potential contamination with other zoonotic pathogens and/or toxins, and serum sickness [32,[34][35][36][37]. For these reasons, plantibodies have been proposed for the treatment of several bacterial (e.g., Salmonella, Streptococcus, Porphyromonas) and viral (e.g., Ebola virus, EBOV; Hepatitis B virus, HBV; Human immunodeficiency virus, HIV; Porcine epidemic diarrhea virus, PEDV; Rabies virus, RABV; West Nile virus, WNV) infections or toxins (e.g., ricin and shiga toxin) [35,[38][39][40][41][42][43][44][45][46]. However, to date, plantibodies have not been used for the treatment of influenza viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…It also looked at current strategies of glycoengineering of plant expression systems to obtain fully humanized proteins for pharmaceutical application. Developments and computational tools for vaccine and antibody production in plants were also discussed recently (Dubey et al, 2018). Critical analysis of the commercial potential of plants for the production of recombinant proteins was also reported in a recent study.…”
Section: Transgenic Plantsmentioning
confidence: 99%